2015
DOI: 10.1002/mrd.22463
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation induces alterations in the epigenome of zygotes, and results in differences in gene expression at the blastocyst stage in mice

Abstract: Gamete and embryo manipulations can result in alterations to the epigenome, and are associated with altered gene expression. The initial objective of this study was to determine the transcript level of several epigenetic modifiers in embryos that had been cultured from the 2-cell stage until the late-blastocyst stage in four culture conditions. Cultured embryos were compared to control, in vivo-produced late blastocysts to ascertain if differences in gene expression existed among the culture conditions; none w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 68 publications
2
52
0
1
Order By: Relevance
“…In addition, their results indicated a higher failure (14%) to develop to the blastocyst stage for embryos obtained from superovulated matings compared to those from spontaneously ovulated matings (5%). Also similar to our findings, the recently published study of Huffman et al [2015] indicated a hypomethylation of the maternal pronucleus of zygotes from superovulated females. However, this study only analyzed maternal pronuclei of PN3 and PN4 embryos and thus lacks a detailed analysis of paternal pronuclei as well as all PN stages.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, their results indicated a higher failure (14%) to develop to the blastocyst stage for embryos obtained from superovulated matings compared to those from spontaneously ovulated matings (5%). Also similar to our findings, the recently published study of Huffman et al [2015] indicated a hypomethylation of the maternal pronucleus of zygotes from superovulated females. However, this study only analyzed maternal pronuclei of PN3 and PN4 embryos and thus lacks a detailed analysis of paternal pronuclei as well as all PN stages.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also used immunofluorescence staining with antibodies against 5mC to document abnormal genome-wide methylation reprogramming in superovu- lated mouse zygotes and 2-cell embryos [Shi and Haaf, 2002;Huffman et al, 2015]. Shi and Haaf [2002] used mouse 2-cell embryos from superovulated females, nonsuperovulated matings, and IVF for 5mC staining and in vitro development analysis up to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found abnormal methylation is particularly involved in ART imprinting disorders related to the context of ASD35. Experiments in animals have suggested that the various steps of the ART procedures such as superovulation, in vitro culture of oocytes or embryo, and IVF might be related to epigenetic defects in the embryos and offspring36. However, abnormal DNA methylation could not be consistently identified in IVF children37.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described anomalies in imprinted gene expression when comparing blastocyst stage embryos developing from superovulated versus naturally ovulated oocytes [1921]; however, subsequent reports found that expression alterations were not associated with abnormalities in methylation patterns [20], and imprinted expression in later stage development was largely normal [22]. Studies investigating postnatal endocrine and reproductive health of offspring resulting from superovulated vs naturally ovulated oocytes found no differences [23, 24].…”
Section: Resultsmentioning
confidence: 99%